函数\(y = 2{x^{ - 3}}{\rm{ - }}3{x^2}\)的导数为( ). A: \( - 6{x^{ - 4}} - 6x\) B: \( - 6{x^{ - 4}} + 6x\) C: \( - 6{x^{ - 3}} - 6{x^3}\) D: \( - 6{x^{ - 3}} + 6{x^3}\)
函数\(y = 2{x^{ - 3}}{\rm{ - }}3{x^2}\)的导数为( ). A: \( - 6{x^{ - 4}} - 6x\) B: \( - 6{x^{ - 4}} + 6x\) C: \( - 6{x^{ - 3}} - 6{x^3}\) D: \( - 6{x^{ - 3}} + 6{x^3}\)
下列计算结果正确的是() A: (﹣2x 2)^3=﹣6x^6 B: x^2x^3 =x^6 C: 6x^4÷3x3 =2x D: x^2 +x^3 =2x^5
下列计算结果正确的是() A: (﹣2x 2)^3=﹣6x^6 B: x^2x^3 =x^6 C: 6x^4÷3x3 =2x D: x^2 +x^3 =2x^5
\( y = 6{x^2},\;y = 6x \)围成的平面图形面积\( A \)= 。______
\( y = 6{x^2},\;y = 6x \)围成的平面图形面积\( A \)= 。______
y=x³ 的二阶导数y''= A: 3x² B: 6x C: 6 D: 0
y=x³ 的二阶导数y''= A: 3x² B: 6x C: 6 D: 0
已知\( y = {x^3} + 2x \),则\( y'' \)为( ). A: \( 3{x^2} \) B: \( 6x \) C: 6 D: 0
已知\( y = {x^3} + 2x \),则\( y'' \)为( ). A: \( 3{x^2} \) B: \( 6x \) C: 6 D: 0
若 $x^3$ 是 $f(x)$ 的一个原函数,则 $f''(x)=$( ). A: $6x$ B: $3x^2$ C: $6$ D: $0$
若 $x^3$ 是 $f(x)$ 的一个原函数,则 $f''(x)=$( ). A: $6x$ B: $3x^2$ C: $6$ D: $0$
6X=8(X-5)为什么X=20?
6X=8(X-5)为什么X=20?
设$f(x)$是三次首一多项式。若$x-1$除$f(x)$余 $1$,$x-2$除$f(x)$余 $2$,$x-3$除$f(x)$余 $3$,则 $f(x)$ =( )。 A: $x^{3}-6x^{2}+12x-6$; B: $x^{3}-6x^{2}+11x-6$; C: $x^{3}-5x^{2}+12x-6$; D: $x^{3}-6x^{2}+12x-5$.
设$f(x)$是三次首一多项式。若$x-1$除$f(x)$余 $1$,$x-2$除$f(x)$余 $2$,$x-3$除$f(x)$余 $3$,则 $f(x)$ =( )。 A: $x^{3}-6x^{2}+12x-6$; B: $x^{3}-6x^{2}+11x-6$; C: $x^{3}-5x^{2}+12x-6$; D: $x^{3}-6x^{2}+12x-5$.
当x趋于0时,(tan(6x)-cos(x)+1)/sin(3x)=()。
当x趋于0时,(tan(6x)-cos(x)+1)/sin(3x)=()。
已知\( y = {x^3}\cos 2x \),则\( y'' \)为( ). A: 0 B: \( 6x\cos 2x{\rm{ + }}12{x^2}\sin 2x - 4{x^3}\cos 2x \) C: \( 6x\cos 2x - 12{x^2}\sin 2x{\rm{ + }}4{x^3}\cos 2x \) D: \( 6x\cos 2x - 12{x^2}\sin 2x - 4{x^3}\cos 2x \)
已知\( y = {x^3}\cos 2x \),则\( y'' \)为( ). A: 0 B: \( 6x\cos 2x{\rm{ + }}12{x^2}\sin 2x - 4{x^3}\cos 2x \) C: \( 6x\cos 2x - 12{x^2}\sin 2x{\rm{ + }}4{x^3}\cos 2x \) D: \( 6x\cos 2x - 12{x^2}\sin 2x - 4{x^3}\cos 2x \)